Competitive profile in school athletes of feminine soccer (Original) (Revista científica Olimpia, 2020)
The sports performance of the athletes and his incidence in his teams' result has been gone into  from several disciplines. In present it contributions documented in entrepreneurial contexts to  create matrix of competitive profile for teams of soccer took investigation like reference and that  way evaluating the national team's athletes Cuban of category of the female sex, that took part  in the Tournament of Development of the Caribe in Trinidad And Tobago in October 2019. The  assessment of the soccer players according to his position: Janitress, center halfbacks, lateral  defenses, fliers of argument, fliers of creation, extremes or foremost center and the their  evaluation of the status out of every one allowed the team's director taking more rational  decisions in the pre-competitive and competitive stages.
Keywords: soccer; the matrix of competitive profile; takes from decisions.